Zona Franca De Ibagué, Beneficios Para La Economía De La Ciudad (2023)
The document seeks to describe and show the different obstacles and problems presented by the Free Trade Zone project in Ibague city, in order to find practical solutions that lead to this idea materializing. Ibague in recent years has been submerged in multiple difficulties that have prevented its development and that have led it to present a backwardness in economic matters, which is why the idea that in Ibague there is a ZF is of utmost importance to reduce unemployment levels, increase investment and competitiveness of a city that has a strategic and privileged location. This research seeks to revive the idea and show the need for Ibague to have an own Free Trade Zone to boost the economic development of the city and Tolima department, since a free trade area like these would attract investment, would be an ideal space to promote local products and would contribute positively to reduce the city unemployment rates